The Destruction of the Canaanites: God, Genocide, and Biblical Interpretation - Dodd, R. Adam (Southwestern journal of theology, 2025)
The Destruction of the Canaanites: God, Genocide, and Biblical Interpretation. By Charlie Trimm. Grand Rapids: William B. Eerdmans Publishing Company, 2022, 127 pp., $ 14.99.